Comparison of Minimally Invasive Operative Treatment with Conservative Treatment for Acute, Minimally Displaced Scaphoid Fractures at 12 Months' Follow-up - Fyllos, Apostolos; Komnos, George; Koutis, Athanasios; Bargiotas, Konstantinos; Varitimidis, Sokratis; Dailiana, Zoe (Journal of Wrist Surgery, 2021)
Background Minimally displaced scaphoid fractures can be challenging to diagnose and treat. Cannulated scaphoid screws have made percutaneous stabilization highly effective.Questions Would minimally invasive operative treatment of minimally displaced scaphoid fractures yield faster return to work when compared with patients treated conservatively? How do functional and patient satisfaction scores compare between the two groups at 12-months follow-up?Patients and Methods Records from 18 patients (mean age 28.6 years) treated surgically were retrospectively reviewed and compared with a group of 10 patients (mean age 33.3 years, p = 0.74) treated nonoperatively. Inclusion criteria were a minimum follow-up period of 12 months and radiographic union. Time to return to work was compared between groups. At 12 months' follow-up, wrist range of motion (ROM) and grip strength were compared, as well as pain, satisfaction, and overall wrist function were evaluated by the visual analogue scale (VAS) and the Mayo modified wrist score (MMWS).Results The mean time to return to work for the operated group was 39.75 days, while for the nonoperated group it was 88.14 days (p = 0.002). At the 12 months' follow-up, mean ROM, grip strength, and VAS score did not differ between groups. The mean MMWS was 98.75 for the operated group and 87.5 for the nonoperated group, indicating a better result in patients treated operatively (p = 0.03). In addition, two failures of instrumentation were recorded, a seldom seen complication.Conclusion Percutaneous fixation of minimally displaced scaphoid fractures allows faster return to work and leaves patients more satisfied with their wrist function compared with plaster immobilization at 12 months' follow-up.Level of evidence This is a Level III, retrospective, case–control study.
Keywords: scaphoid fracture; percutaneous fixation; nonoperative treatment; cannulated screws; cast treatment